2013
DOI: 10.1021/jo401946j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Tetracyanocyclopentadienides from Tetracyanothiophene and Sulfones

Abstract: Tetracyanothiophene and tetracyano-1,4-dithiin react with a leaving group substituted carbon nucleophile such as ethyl benzenesulfonylacetate to afford substituted tetracyanocyclopentadienyl sodium derivatives in moderate to high yields through a putative condensation and desulfurization pathway. Subsequent functional-group transformation reactions on the Cp anion ring provided various C5R(CN)4(-) derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…1). 24) During our previous study, we noticed that salts 1a-f are miscible in polar organic solvents (MeCN, tetrahydrofuran (THF), EtOAc) and can be extracted with organic solvents by partitioning between EtOAc and H 2 O, despite the absence of large hydrophobic functional groups. Such unique lipophilic behavior exhibited by the C 5 R(CN) 4 salts 1a-f stimulated us to explore their catalytic activities in a biphasic solvent system.…”
mentioning
confidence: 99%
“…1). 24) During our previous study, we noticed that salts 1a-f are miscible in polar organic solvents (MeCN, tetrahydrofuran (THF), EtOAc) and can be extracted with organic solvents by partitioning between EtOAc and H 2 O, despite the absence of large hydrophobic functional groups. Such unique lipophilic behavior exhibited by the C 5 R(CN) 4 salts 1a-f stimulated us to explore their catalytic activities in a biphasic solvent system.…”
mentioning
confidence: 99%
“…Dimethyldioctylammonium chloride (as a mixture with decyldimethyloctylammonium chloride and didecyldimethylammonium chloride) was purchased from Waterstone Technology, LLC, and was purified before use by washing an aqueous solution of the compound with n ‐hexane, extracting with CHCl 3 , and then washing the organic layer with an aqueous solution of HCl. Sodium pentacyanocyclopentadienide (PCCp − ) was synthesized according to a literature procedure . 1 H NMR spectra were recorded on a JEOL ECA‐600 600 MHz spectrometer and referenced to the solvent signal.…”
Section: Methodsmentioning
confidence: 99%
“…The Cl À ion pairs were suitable for furthera nion exchange because of the high affinity of Cl À for inorganic cations. In fact, Au III complexes as Cl À ion pairs were converted to av ariety of ion pairs utilizing BF 4 À ,P F 6 À ,a nd pentacyanocyclopentadienide (PCCp À ), [12] by treatment with 3equiv of Ag + (BF 4 À and PF 6 À )o rN a + (PCCp À )s alts, followed by the removal of metal chlorides, column chromatography with silica gel and recrystallization (Scheme 2). The ion pairs synthesized in this study, which were identified by spectroscopic ande lemental analyses, showedn os ignificant interactions between cationic Au III complexes and coexisting anions in 1 HNMR at 20 8C.…”
Section: Anion Exchange Providing Av Ariety Of Ion-pairing Assembliesmentioning
confidence: 99%